Preliminary assessment of microfibers amount in textile wastewater - AKYILDIZ, SİNEM HAZAL; YALÇIN, BAHATTİN (My University, 2022)
Textile wastewater is a complex mixture of inorganic compounds, polymers, organic products, dyes, and microfibers (MFs), including microplastics (MPs) and natural fibers. The treatment of textile wastewater, which contains a significant share of MFs, is of great importance to prevent the release of MPs in the environment. MPs analysis requires multiple phases of pretreatment (to eliminate the organic compounds), separation of the MFs from the water, and identification of the MPs among the MFs. This work presents the preliminary results of a research aimed at exploring two issues. Firstly, the pretreatment (through Fenton,H2O2, HCl, KOH and NaOH, applied at 25 °C for 5 days and 60 °C for 6 hours) of artificial textile wastewater, evaluating the effect of the different conditions on the MFs and the MPs. Secondly, the separation of MFs from a real textile wastewater sample through different processes (centrifugation, sink-float & filtration, filtration). The results of the pretreatment tests revealed Fenton, HCl, andH2O2at 25 °C for 5 days as the best performing chemicals and conditions. Considering the results of the separation tests, filtration gave back the best removal of the MFs from wastewater compared to centrifugation and sink-float and filtration, which left some MFs in the supernatant/float and in the sediment/sink. In conclusion, these preliminary results may be useful to further explore the detection of MFs and MPs in textile wastewater.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); centrifugation; filtration; microfibers; microplastics; pretreatment; separation; textile wastewater